Pemanfaatan buku tulis sisa menjadi buku tulis baru di SD Nurul Ulum Dusun Wire Desa Ngemplak, Baureno, Bojonegoro - Neneng Rika Jazilatul Kholidah; Rika Pristian Fitri Astuti; Sarjono Sarjono (Yumary: Jurnal Pengabdian kepada Masyarakat, 2020)
Purpose: This PKM aimed to increase knowledge and conduct training the students of SD Nurul Ulum on how to process leftover notebooks into new useful notebooks. The method in PKM is a lecture method to provide knowledge as well as an understanding of the benefits of the remaining notebook. Method: The team also uses experimental methods by conducting experiments to provide various examples in processing leftover notebooks into new notebooks by considering design aspects. Results: These community service results are 1) Students gain experience on how to process leftover notebooks into new notebooks, 2) Students can innovate in making leftover notebooks with their creative ideas. Conclusion: The conclusion from the implementation of PKM is that overall, there is an increase in students' understanding and knowledge in processing leftover notebooks into new notebooks. Keywords: Utilization, Remaining notebooks, Students, New notebooks